Cigarette smoke causes acute airway disease and exacerbates chronic obstructive lung disease in neonatal mice - Jia, Jie; Conlon, Thomas M.; Ballester Lopez, Carolina; Seimetz, Michael; Bednorz, Mariola; Zhou-Suckow, Zhe; Weissmann, Norbert; Eickelberg, Oliver; Mall, Marcus A.; Yildirim, Ali Önder (American journal of physiology. Lung cellular and molecular physiology, 2016)
Epidemiological evidence demonstrates a strong link between postnatal cigarette smoke (CS) exposure and increased respiratory morbidity in young children. However, how CS induces early onset airway disease in young children, and how it interacts with endogenous risk factors, remains poorly understood. We, therefore, exposed 10-day-old neonatal wild-type and β-epithelial sodium ion channel (β-ENaC)-transgenic mice with cystic fibrosis-like lung disease to CS for 4 days. Neonatal wild-type mice exposed to CS demonstrated increased numbers of macrophages and neutrophils in the bronchoalveolar lavage fluid (BALF), which was accompanied by increased levels of Mmp12 and Cxcl1. BALF from β-ENaC-transgenic mice contained greater numbers of macrophages, which did not increase following acute CS exposure; however, there was significant increase in airway neutrophilia compared with filtered air transgenic and CS-exposed wild-type controls. Interestingly, wild-type and β-ENaC-transgenic mice demonstrated epithelial airway and vascular remodeling following CS exposure. Morphometric analysis of lung sections revealed that CS exposure caused increased mucus accumulation in the airway lumen of neonatal β-ENaC-transgenic mice compared with wild-type controls, which was accompanied by an increase in the number of goblet cells and Muc5ac upregulation. We conclude that short-term CS exposure 1) induces acute airway disease with airway epithelial and vascular remodeling in neonatal wild-type mice; and 2) exacerbates airway inflammation, mucus hypersecretion, and mucus plugging in neonatal β-ENaC-transgenic mice with chronic lung disease. Our results in neonatal mice suggest that young children may be highly susceptible to develop airway disease in response to tobacco smoke exposure, and that adverse effects may be aggravated in children with underlying chronic lung diseases.
Gesehen am 06.05.2020